Sources of Genetic Resistance to Cercospora guizoticola induced Leaf Spot in Niger (Guizotia abyssinica (L.F.) Cass) - Subedi, Subash; Dhakal, Shubhechchha; Neupane, Saraswati; Yadav, Sailendra (Journal of the Plant Protection Society, 2024)
Niger (Guizotia abyssinica (L.F.) Cass) is a promising but underexplored oilseed crop in Nepal, with considerable expansion potential. However, it faces a significant threat from leaf spot disease, caused by Cercospora guizoticola, resulting in notable yield reductions. This study aimed to identify genetic sources of resistance to this pathogen. Sixty-three niger genotypes, including resistant check ACC#5320 and susceptible check ACC#5355, underwent disease resistance screening over two years (2022-2023) in field disease screening nurseries at the Oilseed Research Program, Sarlahi, using an incomplete block design. Each block contained nine genotypes, replicated twice. Disease severity, yield, and yield-attributing traits were assessed. Significant variations in disease and yield traits were observed among the genotypes over the years. While only 10% exhibited resistance, 34% showed moderate resistance with minimal symptoms compared to susceptible types. None were immune, with 22 genotypes (36%) classified as susceptible and 20% highly susceptible. A significant negative correlation (P≤0.05) between disease severity and grain yield was evident. Genotypes ICN Lumle 3000, G-51, G-5, ACC#5363, ACC#5323, and ACC#5319 demonstrated both high yielding (>1 t/ha) and resistance to Cercospora leaf spot, offering valuable genetic resources for enhancing niger’s resilience to this disease through breeding initiatives.